The Effect of Flipbook-Assisted Discovery Learning on Student Learning Achievement - Puput Suriyah; Sujiran; Ari Indriani; Boedy Irhadtanto; Ali Noeruddin; Muhammad Rinov Cuhanazriansyah; Dina Mariana (Jurnal Pendidikan Edutama, 2026)
Low mathematics learning achievement and minimal use of learning media are problems in mathematics learning, especially in the subject of quadrilateral shapes. This study aims to determine the effect of the discovery learning model assisted by flipbooks on the mathematics learning achievement of seventh-grade students at SMP Negeri 1 Rengel. This study used a quasi-experimental method with a non-equivalent control group design. The research subjects consisted of class VII C as the experimental class and class VII A as the control class. Data were collected through learning achievement tests and analysed using the t-test. The results showed that the learning achievement of students who participated in discovery learning assisted by flipbooks was higher than that of students who participated in conventional learning. Thus, the discovery learning model assisted by flipbooks had a positive effect on students' mathematics learning achievement.